Properties and Macromolecular Structure of Unacetylated and Acetylated Nata de Coco - Cuyegkeng, Ma. Assunta C (Archīum Ateneo, 1997)
This study aims to gain more insight into the supramolecular structure of the cellulose in nata de coco, and to compare its ability to be modified with the known types of cellulose. The investigations were done using IR spectroscopy and thennal analysis. The IR spectra of microcrystalline cellulose were identical to cellulose spectra. However, those of dried nata de coco cellulose showed additional peaks that indicated a loss of inter- and intra-sheet hydrogen bonding, usually extensive in other cellulose forms where sheets are the prevalent secondary structures. This kind of structure would be consistent with the necessary framework for gel formation. Details in the fingerprint region further supported a different macromolecular structure from the microcrystalline cellulose. Acetylation of the fresh and pressed-and-dried nata de coco yielded only partial acetylation, as indicated by the C=O stretching as well as the remaining broad OR-stretch. Acetylated samples showed reduced water retention capacities, and were more prone to variable water retention characteristics during pH changes. The DSC and TGA behavi or of microcrystalline cellulose, acetylated and unacetylated forms of nata de coco showed differences in the macromolecular structures, as well as in stability of the material.